FORMULATION, OPTIMIZATION, AND EVALUATION OF SITAGLIPTIN AND SIMVASTATIN RAPIDLY DISSOLVING TABLETS - Bayoumi, Asmaa A. (International Journal of Applied Pharmaceutics, 2018)
Objective: The scope of this work was to formulate sitagliptin and simvastatin rapidly dissolving tablets. However, simvastatin is practically insoluble in water. For improving its poor oral bioavailability and with the aim of facilitating administration to patients facing problems with swallowing rapidly dissolving tablets were prepared Methods: Tablets were prepared using superdisintegrant addition technique using croscarmellose sodium (Ac-di-sol), sodium starch glycolate (explotab) and crospovidone in different percentages. Evaluation tests such as weight variation, thickness, and content variation, and friability, disintegration, wetting time, in vitro dispersion and in vitro dissolution were carried out. Results: The results showed that the presence of crospovidone could enhance the dissolution rate of simvastatin greatly. The best-optimized formulae found were that F8, F9, and F10 which showed good disintegration and the dissolution rate of simvastatin and sitagliptin was more than 90% after 10 min while the dissolution rate for simvastatin and sitagliptin pure standards was 12% and 30%, respectively after 10 min. Conclusion: Some tablet formulae showed acceptable pharmacotechnical properties and complied with compendium requirements. Results of dissolution studies revealed that F8-F10 showed an increase in the dissolved sitagliptin and simvastatin to be more than 90% after 10 min.Â